2007
DOI: 10.1029/2006jd007984
|View full text |Cite
|
Sign up to set email alerts
|

A case study of boundary layer ventilation by convection and coastal processes

Abstract: [1] It is often assumed that ventilation of the atmospheric boundary layer is weak in the absence of fronts, but is this always true? In this paper we investigate the processes responsible for ventilation of the atmospheric boundary layer during a nonfrontal day that occurred on 9 May 2005 using the UK Met Office Unified Model. Pollution sources are represented by the constant emission of a passive tracer everywhere over land. The ventilation processes observed include shallow convection, turbulent mixing foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 28 publications
6
39
0
Order By: Relevance
“…Over LIS, residual layers have frequently been found in summer months, when land-sea temperature contrasts are larger [41] and observed as reservoirs for boundary layer trace gas pollutants during air quality episodes along the East Coast [42]. In the study conducted here, data further suggested that the residual layer facilitated the long-range transport achieved by the plume through its advection into the lower troposphere and over the marine boundary layer, thus, detaching it from surface interactions in a similar fashion to that described by Dacre et al [15] and Fochesatto et al [43].…”
Section: Physical Structure Of the Plume Layersupporting
confidence: 84%
See 2 more Smart Citations
“…Over LIS, residual layers have frequently been found in summer months, when land-sea temperature contrasts are larger [41] and observed as reservoirs for boundary layer trace gas pollutants during air quality episodes along the East Coast [42]. In the study conducted here, data further suggested that the residual layer facilitated the long-range transport achieved by the plume through its advection into the lower troposphere and over the marine boundary layer, thus, detaching it from surface interactions in a similar fashion to that described by Dacre et al [15] and Fochesatto et al [43].…”
Section: Physical Structure Of the Plume Layersupporting
confidence: 84%
“…In this, decoupling of the continental airmass, usually through the formation of a residual layer following the diurnal fluctuation of the daytime boundary layer, is the ventilation mechanism for the plume's release. Very similar scenarios have recently detailed in the coastal atmospheric study by Dacre et al [15] and observed during previous field campaigns in the North Atlantic, as reported by Gong et al [52]. As these and other related studies have pointed out, the coastal IBL structure can play a significant role in low-altitude regional transport, particularly over the GOM [3,9,13,14,52].…”
Section: /21~daysupporting
confidence: 83%
See 1 more Smart Citation
“…Both forms of convective activity can lead to ventilation of the boundary layer and rapid vertical transport on a time-scale of hours into the free troposphere (e.g. Gimson, 1997;Dacre et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the term "coastal outflow layer" will be used to describe the decoupling of pollution from the surface via the formation of an internal stable BL which occurs when there is horizontal transport from land to sea and the land BL is deeper than the MBL (as is typically the case on nonfrontal summer days) (Dacre et al, 2007). The coastal outflow layer lies above the MBL (H MBL ) but below the maximum height that the continental BL reaches during its diurnal cycle (H max ).…”
Section: L Peake Et Al: Coastal Outflowmentioning
confidence: 99%